The Effect of Health Insurance on Emergency Department Visits: Evidence from an Age-Based Eligibility Threshold - Anderson, Michael L.; Dobkin, Carlos; Gross, Tal (The Review of Economics and Statistics, 2014)
Health insurance affects the rate at which individuals visit hospitals and emergency departments (EDs). We identify the causal effect of losing health insurance using a regression discontinuity design. We compare individuals just before and after their twenty third birthday, which insurers have used as a cutoff after which students are no longer eligible for their parents' health insurance: 1.5% of young adults lose their health insurance upon turning 23, and this transition leads to a 1.6% decrease in ED visits and a 0.8% decrease in hospital stays. We discuss why these estimates are larger than those observed among teenage populations.